Use of home health and other healthcare delivery pathways among privately insured patients with and without treatment-resistant depression. (3rd May 2020) - Pilon, Dominic; Szukis, Holly; Singer, David; Morrison, Laura; Sheehan, John J.; Lefebvre, Patrick
Abstract: Objective: To assess the real-world use of home health services (HHS) among patients with major depressive disorder (MDD) with and without treatment-resistant depression (TRD). Methods: Adults (18–64 years) from a commercial claims database (07/2009 to 03/2015) were categorized into three cohorts: "TRD"( N  = 6411), "non-TRD MDD"( N  = 33, 068), "non-MDD"( N  = 149, 884) stratified based on use of HHS (HHS vs. no-HHS). Healthcare resource utilization (HRU) and costs were evaluated up to two years following the first antidepressant pharmacy claim using descriptive statistics. HRU (e.g. inpatient, outpatient, emergency department visits) and costs were measured per-patient-per-year (PPPY) in 2015 USD. Results: During the follow-up period, 18.0% of TRD, 12.4% of non-TRD MDD, and 6.5% of non-MDD patients received HHS. Mean all-cause healthcare costs PPPY were numerically higher among patients with HHS use. Among the TRD cohort, patients using HHS had healthcare costs of $40, 040 PPPY while patients with TRD and no-HHS had healthcare costs of $12, 272 PPPY. Within the non-TRD MDD cohort, HHS users incurred healthcare costs of $28, 767 PPPY and non-HHS users incurred costs of $7227 PPPY. Patients without MDD who used HHS had annual healthcare costs of $22, 340 while non-MDD patients who did not use HHS had healthcare costs of $3479 PPPY. However, among HHS users, HHS costs represented a relatively small proportion of total healthcare costs. Conclusions: The high proportion of TRD patients using HHS suggests it is a utilized healthcare delivery pathway by TRD patients.